An Improved Synthesis of Urea Derivatives from N-Acylbenzotriazole via Curtius Rearrangement - Singh, Anoop S.; Agrahari, Anand K.; Singh, Sumit K.; Yadav, Mangal S.; Tiwari, Vinod K. (Synthesis, 2019)
The good leaving tendency of the benzotriazole moiety has been exploited for the synthesis of symmetric, unsymmetric, N-acyl, and cyclic ureas in good yields from N-acylbenzotriazoles by treating the latter with various amines in the presence of TMSN3/Et3N in a sealed tube. The salient features of the devised protocol includes the high-yield, mild, metal-free, one-pot reaction conditions, and short reaction time. Furthermore, in many cases, no column chromatography is required for the purification.
Keywords: ureas; benzotriazole; Curtius rearrangement; N-acylbenzotriazole; introduction